GhWRKY68 Reduces Resistance to Salt and Drought in Transgenic Nicotiana benthamiana - Jia, Haihong (Public Library of Science, 2015)

(untitled) (PLoS One)
The WRKY transcription factors modulate numerous physiological processes, including plant growth, development and responses to various environmental stresses. Currently, our understanding of the functions of the majority of the WRKY family members and their possible roles in signalling crosstalk is limited. In particular, very few WRKYs have been identified and characterised from an economically important crop, cotton. In this study, we characterised a novel group IIc WRKY gene, GhWRKY68, which is induced by different abiotic stresses and multiple defence-related signalling molecules. The β-glucuronidase activity driven by the GhWRKY68 promoter was enhanced after exposure to drought, salt, abscisic acid (ABA) and H(2)O(2). The overexpression of GhWRKY68 in Nicotiana benthamiana reduced resistance to drought and salt and affected several physiological indices. GhWRKY68 may mediate salt and drought responses by modulating ABA content and enhancing the transcript levels of ABA-responsive genes. GhWRKY68-overexpressing plants exhibited reduced tolerance to oxidative stress after drought and salt stress treatments, which correlated with the accumulation of reactive oxygen species (ROS), reduced enzyme activities, elevated malondialdehyde (MDA) content and altered ROS-related gene expression. These results indicate that GhWRKY68 is a transcription factor that responds to drought and salt stresses by regulating ABA signalling and modulating cellular ROS.